Posttransplant Solid Organ Malignancies in Lung Transplant Recipients: A Single-center Experience and Review of the Literature. Issue 6 (November 2016) - Bennett, David; Fossi, Antonella; Refini, Rosa Metella; Gentili, Francesco; Luzzi, Luca; Voltolini, Luca; Paladini, Piero; Mazzei, Maria Antonietta; Rottoli, Paola
Purpose: Solid-organ tumor incidences are higher in solid organ transplant patients than in the general population. The aim of this study was to analyze solid-organ tumor frequency and characteristics in a population of lung transplant patients and provide a brief review of the literature. Methods: A retrospective analysis was conducted of all patients who underwent a lung transplant in the Lung Transplant Program at the University Hospital of Siena, Italy, from 2001 to 2014 (n = 119). Patients' demographics, pretransplant characteristics, immunosuppressive therapy, and infectious factors were recorded. Results: Nine patients with a median age of 59.0 years (range 50–63) of our cohort developed a solid-organ tumor (7.5%). Most of the patients experienced nonmelanoma skin cancer (44.4%); the others were diagnosed with lung cancer (22.2%), breast cancer (22.2%), and colon-rectal cancer (11.2%). The median time from transplantation to tumor diagnosis was 895.0 days (range 321–2046). No differences in pretransplant characteristics, immunosuppressive therapy, or infectious factors were found between patients who developed solid organ tumors and those who did not. Conclusions: The present study confirmed that de novo malignancies are a major issue in lung transplant patients; in particular, skin and lung cancers demonstrated a higher incidence rate. Oncologic treatment of these patients is complex, requiring close collaboration between the transplant team and oncologist. Strict screening programs are key factors for an early diagnosis and to allow for prompt treatment resulting in a better outcome.